Integrating indigenous knowledge in modern agriculture: Challenges and opportunities - Tarun, Kshatriya T; Thamizh, Vendan R; Rajeswari, C (Plant Science Today, 2025)
Around 10000 years ago, humans began domesticating plants and understanding the role of weather and soil in agriculture. Over generations, they developed environmentally friendly farming practices, that sustained productivity while preserving local ecosystems. This historical perspective underscores the value of indigenous knowledge in developing alternative resource management approaches. Traditional techniques, refined through centuries, hold immense significance and must be safeguarded from extinction. These methods are eco-friendly and community-centric, offering viable solutions to contemporary agricultural challenges, including climate change, resource depletion and food insecurity. Their low-cost, sustainable nature makes them an essential complement to modern high-input farming. Integrating these practices with contemporary agriculture can foster resilient, environmentally sound and culturally significant farming systems. However, to fully leverage their potential, further research scientific validation and systematic documentation are imperative. Research institutions, NGOs and policymakers must collaborate to revive, adapt and disseminate these techniques among farming communities. This synergy between traditional wisdom and modern innovation can bridge the gap, ensuring a more sustainable agricultural future. By recognizing, validating and integrating traditional agricultural knowledge, we can create robust farming systems that preserve biodiversity, improve resilience and support food security for future generations.